Implementasi Strategi Load Shedding Berbasis Under Frequency Relay untuk Meningkatkan Kestabilan Sistem Distribusi Listrik di PT Pertamina Pendopo Field - Alfaresi, Bengawan; Saputra, Heri; Ardianto, Feby (Faculty of Engineering, Universitas Serambi Mekkah, 2026)
Disturbances in the stability of the electric power system due to frequency drops caused by disturbances at power plants often occur in the community. This causes damage to electrical equipment, especially those sensitive to frequency. This study discusses the application of the Under Frequency Load Shedding (UFLS) method as a solution to overcome this problem. The study was conducted at PT. Pertamina Pendopo Field, which uses an independent electrical system with several gas-fueled generator units. The method used in this study is a case study with a simulation based on ETAP 19.0.1 software to analyze the system response to disturbances. Calculations were made on the rate of frequency drop and the amount of load that must be shed to maintain system stability. The simulation showed that gradual load shedding of 720 kW with shedding stages at 58.4 Hz and 58.1 Hz frequencies successfully returned the system frequency to normal conditions without shedding critical loads such as production loads. The results of the study indicate that the gradual and selective application of UFLS is effective in maintaining the stability of the electric power system and preventing total blackouts. This scheme also supports the operational continuity of industrial facilities by prioritizing the continuity of power supply to critical loads.